EDUKASI TENTANG PENTINGNYA SUPLEMENTASI PROBIOTIK UNTUK MENJAGA IMUNITAS DI MASA PANDEMI COVID-19 - Reza Anindita; Dede Dwi Nathalia; Melania Perwitasari; Intan Kurnia Putri; Maya Uzia Beandrade (Universitas Mataram, 2022)
The community death rate due to Covid-19 is 2.58%. This percentage places Indonesia as the second highest CFR Covid-19 score in Southeast Asia. The highest death rate was in the age group > 65 years, which was 48.7%. Therefore, efforts to deal with Covid-19 are needed through education in Community Service activities (PKM) in the form of the importance of consuming probiotics to maintain endurance during the Covid-19 pandemic. The purpose of this PKM is to provide education about types of probiotics as a supplement to prevent Covid-19. Education also informs about the proper rules regarding the consumption of probiotics as an effort to increase endurance during the Covid-19 pandemic. This method of activity was adapted to the COVID-19 pandemic which required online meeting policies. The preparatory stage is carried out by compiling interesting and communicative material in the form of attractive and communicative power points, videos and posters. The implementation phase is carried out online in the form of a webinar. The evaluation evaluation stage is carried out by looking at the number of participants who are actively participating in the PKM webinar. Publication of PKM activities is carried out through Instagram and WhatsApp social media. Specifically on WhatsApp, a group of SMA/SMK teachers was created to facilitate the dissemination of information about Mitra Keluarga STIKes PKM activities. The number of participants who took part in this PKM webinar was 142 people. As for this PKM, the community was able to understand educational material as evidenced by the average pre-test and post-test scores of the 142 participants in this activity sequentially increasing from 58 to 81 with a percentage increase of 55%. The conclusion from this activity is that the community is able to understand educational material in online PKM webinars. The material is the effectiveness of consuming probiotics in preventing Covid-19.